Increasing power output and movement optimization in cycling: Insights from a fully instrumented ergometer - Costes, A.; Turpin, N. A.; Villeger, D.; Moretto, P.; Watier, B. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
We hypothesized that the saddle vertical force would be a critical parameter to explain the sitto-stand transition during cycling. Twenty-five participants were required to pedal at six different powers ranging from 20 (1.6 ± 0.3 W.kg-1) to 120% (9.6 ± 1.6 W.kg-1) of their Sit-to-Stand Transition Power (SSTP) at 90 RPM. Five 6-component sensors recorded the loads applied on the saddle, pedals and handlebars. The results showed that the saddle vertical force decreased with increasing cycling power, from a static position on the bicycle (5.30 ± 0.50 N.kg-1) to 120% of SSTP (0.68 ± 0.49 N.kg-1). Pedal and handlebar force directions were reversed around SSTP, suggesting that the seated position may become constraining in these pedalling conditions. These results suggest that the saddle vertical reaction force may be predictive of the sit-to-stand transition in cycling, and that pedalling in the seated position at high crank forces add constraints on the cyclist, explaining the spontaneous change in coordination mode.